USLE Estimation for Potential Erosion at Wae Heru Watershed and Wae Tonahitu Watershed, Ambon Island, Indonesia - Halvina Grasela Saiya; Suprapto Dibyosaputro; Sigit Herumurti Budi Santosa (Indonesian Journal of Geography, 2016)
Abstract Calculate the potential erosion at Wae Heru and Wae Tonahitu Watershed aims to map and assess the potential erosion, in order to be a scientific consideration for exploration and development. The method is a field survey to determine the forms of land use and other forms of conservation efforts; secondary data collection, i.e. soil data, rainfall data, slopes data and data interpretation from Geo Eye satellite imagery in 2012. Further data processing used USLE formula with ArcGIS program. The results showed that the potential erosion of Wae Heru Watershed and Wae Tonahitu Watershed are in very light potential class. This is because the conditions in the upstream are still forested largely. However, at the downstream potential for erosion is vary, i.e. light class, moderate class, heavy class and very heavy class. This is because the conditions in the downstream undergo conversion into settlement, moor, garden, open land and sand mining. Abstrak Menghitung potensi erosi di Wae Heru dan Wae Tonahitu Daerah Aliran Sungai bertujuan untuk memetakan dan menilai potensi erosi, agar menjadi pertimbangan ilmiah untuk eksplorasi dan pengembangan. Metode ini adalah survei lapangan untuk menentukan bentuk penggunaan lahan dan bentuk lain dari upaya konservasi; pengumpulan data sekunder, data tanah yaitu, data curah hujan, data yang lereng dan interpretasi data dari citra satelit Geo Eye pada tahun 2012. pengolahan data lebih lanjut digunakan rumus USLE program ArcGIS. Hasil penelitian menunjukkan bahwa erosi potensi Wae Heru DAS dan Wae Tonahitu Daerah Aliran Sungai di kelas potensial sangat ringan. Hal ini karena kondisi di hulu masih berhutan sebagian besar. Namun, pada potensi hilir erosi adalah bervariasi, yaitu kelas ringan, kelas menengah, kelas berat dan kelas yang sangat berat. Hal ini karena kondisi di hilir mengalami konversi menjadi pemukiman, tegalan, kebun, lahan terbuka dan penambangan pasir.